Characterization of the spatial distribution of irradiance and spectrum in concentrating photovoltaic systems and their effect on multi‐junction solar cells. (19th October 2011) - Victoria, M.; Herrero, R.; Domínguez, C.; Antón, I.; Askins, S.; Sala, G.
ABSTRACT The irradiance and spectral distribution cast on the cell by a concentrating photovoltaic system, typically made up of a primary Fresnel lens and a secondary stage optical element, is dependent on many factors, and these distributions in turn influence the electrical performance of the cell. In this paper, the effect of spatial and spectral non‐uniform irradiance distribution on multi‐junction solar cell performance was analyzed using an integrated approach. Irradiance and spectral distributions were obtained by means of ray‐tracing simulation and by direct imaging at a range of cell‐to‐lens distances. At the same positions, I–V curves were measured and compared in order to evaluate non‐uniformity effects on cell performance. The procedure was applied to three different optical systems comprised a Fresnel lens with a secondary optical element consisting of either a pyramid, a dome, or a bare cell. Copyright © 2011 John Wiley & Sons, Ltd.